(untitled) (International Journal of Food and Nutritional Sciences, 2023)
In order to protect the works of both individuals and companies, intellectual property rights, or IPRs, are essential. They guarantee that creators and innovators are properly acknowledged and compensated for their contributions. IPRs are essential for encouraging innovation, promoting creativity, and drawing in investment since they offer exclusive rights over trade secrets, trademarks, creative creations, and inventions. Businesses and people are encouraged to invest in R&D by these legal safeguards, which promotes technological breakthroughs and general economic prosperity.